Kuasa Feminin vs Konstruksi Patriarkal: Studi Komparatif dalam Perspektif Simone de Beauvoir - Tiffany , Rehilia; Khairunnisa , Nia; Mawarni , Cantika; Hadawiyah, Andina; Nursalassaty, Nursalassaty; Sitompul, Monalisa Senada (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze how women are portrayed in two legends, namely Nyi Roro Kidul and Dewi Anjani, from the perspective of Simone de Beauvoir's existential feminism. This study focuses on three main mechanisms proposed by Beauvoir, namely stereotypes, subordination, and objectification of women. The method used is descriptive qualitative, with data sources in the form of legend texts and relevant academic references. The data analysis process was carried out using the Miles, Huberman, and Saldaña model, which consists of three stages, namely data reduction, data presentation, and conclusion drawing. The results show that both legends display the same patriarchal construction patterns, such as labeling women negatively, placing women in a social position below men, and viewing women's bodies only as cultural symbols and objects. However, both characters also display different forms of female power. Nyi Roro Kidul is depicted as a supernatural and powerful figure despite being objectified, while Dewi Anjani manages to gain sovereignty after breaking free from the patriarchal structure. These findings show that legends play a role in reproducing and negotiating gender ideology, making it important to critically analyze folklore as part of the culture that shapes society's perceptions of women.